Analysis of optic nerve head parameters, retinal nerve fiber layers and macular thickness in helicobacter pylori infection patients - Zamli, Ahmad Kamal Ghanimi (2019)
Background Helicobacter pylori (H. pylori) has been known to have extra-gastric manifestations. The eye was not spared as in recent years studies have shown the association of H. pylori with glaucoma and central serous chorioretinopathy (CSCR). Both diseases posed a significant threat to the vision and can lead to blindness if untreated. This study aimed to evaluate the optic nerve head (ONH) parameters, retinal nerve fibre layers (RNFL) and macular thickness in patients with Helicobacter pylori infection and comparing it with controls. Methods: A randomised comparative cross-sectional study was conducted at Endoscopic Unit. of Hospital Universiti Sains Malaysia from March 2017 to June 2018. The ONH parameters, RNFL and macular thickness was taken using SD-Cirrus OCT examinations. Statistical analysis was done using Statistical Package for the Social Science, Version 24. Results: A total of 80 patients were included in this study. Forty candidates with H. pylori infection were grouped under H. pylori positive group while another 40 healthy adults were grouped under controls. The mean age for H. pylori positive patients were 52.43  15.67 years old. There were asymmetrical RNFL thickness in H. pylori group, 81.73%  12.81 (p = 0.015). No significant differences were observed on other ONH and RNFL parameters. Macula thickness parameters showed an increase in thickness at the inferior inner, nasal inner and nasal outer quadrant after controlling for age and gender. Conclusion: This study showed that there is asymmetrical RNFL thickness in H. pylori patients and may suggest the possibility of optic nerve damage. There was also an increase in several areas of retinal thickening in patients with H. pylori infection patients.